PELAKSANAAN PEMBERIAN REMISI BAGI WARGA BINAAN PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KHUSUS NARKOTIKA KELAS III SAWAHLUNTO - Zulfikri Anshori; Sukmareni Sukmareni; Syaiful Munandar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The granting of remission is a right for inmates who are serving a criminal term in a Correctional Institution. In the Sawahlunto Class III Narcotics Special Penitentiary, the provision of remissions for inmates of the correctional facility has been running smoothly although there are several obstacles encountered, one of which is the delay in the remission decree (SK) received by the inmates of the correctional facility concerned so that the calculation of remissions for residents cannot be carried out. the correctional facility. One of the efforts made by Correctional Officers at the Class III Narcotics Special Penitentiary in Sawahlunto is by re-proposing the remission of the prisoner's inmates under the name of administrative delay remission. This research is descriptive in nature and the type of empirical juridical research is research that is descriptive in nature and aims to examine statutory provisions and their application, as well as data obtained from documentation studies and interviews conducted at the Class III Narcotics Correctional Institution Sawahlunto then analyzed to answer problems in research related to the problem of implementing remissions. The results of the study show that the implementation of granting remissions for inmates of correctional institutions has been carried out properly in accordance with statutory regulations, but there are still some obstacles.